Al-Faslu wa al-Waslu Baina al-Qudama’ wa al-Muhaddhitsin - Aleue, Entea Abas; Muhyaldeen, Noor Khald; Mgeser, Uoreb Kadhim; Mhmod, Hanan Sade; Nama, Gnan Hosen (Dzil Majaz: Journal of Arabic Literature, 2024)
The topic of separation and connection is one of the topics that aroused the ire of rhetoricians, and they cared about this subject a lot. The fact that the contextual textual significance is what necessitates separation or connection, and we will talk about this matter in its place in the research, followed by Al-Sakaki and then Al-Qazwini in detailing the talk about separation and connection and explaining their importance in semantic contextual creativity. Linguistic speakers followed them in extensive opinions on separation and connection in their rhetorical and stylistic blogs. Among them is Muhammad Khatabi in his book Linguistics of Discourse. In this research, we aim to talk about separation and connection among ancient and modern scholars, highlighting the extent to which modern scholars were influenced by the ancients in their rhetorical views, as well as demonstrating the stylistic-aesthetic effectiveness of this style through procedural analysis of a literary text and demonstrating the effectiveness of separation and connection in textual creativity and aesthetics of textual significance. in it.